Attitudes Towards Artificial Intelligence and Academic Performance Perceptions of Academicians Working in the Field of Sports Sciences - Karahüseyinoğlu, M. Fatih; Gacar, Atalay; Kırdemir, Ayberk; Vaizoğlu, Zeki (Necmettin Erbakan Üniversitesi, 2025)
In this study, it was aimed to examine the relationship between the attitudes of academicians working in Faculties of Sport Sciences towards the use of artificial intelligence and their academic performance. Relational survey model was used in the research, which was designed as a quantitative research. In the study, “General Attitude Scale towards Artificial Intelligence” and “Academic Performance Perception Scale” were used. The sample of the study consisted of 184 academicians, 107 of whom were male and 77 of whom were female, working in the Faculties of Sport Sciences in the Eastern Anatolia Region. Independent sample t-test, one-way analysis of variance (ANOVA) test and Pearson correlation tests were used to analyze the data. As a result of the analyzes, it was concluded that the general attitudes of the academicians working in the Faculties of Sport Sciences towards artificial intelligence were positive. However, it was also found that their perceptions towards academic performance were above average. It was determined that there was a significant positive relationship between the positive attitude sub-dimension of the general attitude scale towards artificial intelligence and the perception scale for academic performance of academicians working in the Faculties of Sport Sciences. The academic performance perceptions of academics who are uncomfortable with the knowledge that they use artificial intelligence are lower than academics who are not uncomfortable with the knowledge that they use artificial intelligence. It was found that the academic performance perceptions of academics who had previously used artificial intelligence were higher. The results show that academics' attitude towards artificial intelligence technologies has the potential to have a significant impact on academic performance.

Bu araştırmada, Spor Bilimleri Fakültelerinde görev yapan akademisyenlerin yapay zeka kullanımına yönelik tutumları ile akademik performansları arasındaki ilişkinin incelenmesi amaçlanmıştır. Nicel araştırma olarak kurgulanan araştırmada ilişkisel tarama modeli kullanılmıştır. Araştırmada, “Yapay Zekaya Yönelik Genel Tutum Ölçeği” ve “Akademik Performans Algı Ölçeği” kullanılmıştır. Araştırmanın örneklemini, Doğu Anadolu Bölgesi Spor Bilimleri Fakülterinde görev yapan 107’si erkek, 77’si kadın olmak üzere toplam 184 akademisyen oluşturmaktadır. Verilerin analizinde bağımsız örneklem t-testi, tek yönlü varyans analizi (ANOVA) testi ve pearson korelasyon testlerinden yararlanılmıştır. Analizler sonucunda, Spor Bilimleri Fakültelerinde görev yapan akademisyenlerin yapay zekaya yönelik genel tutumlarının olumlu şekilde olduğu sonucuna ulaşılmıştır. Bununla birlikte, akademik performansa yönelik algılarının da ortalamanın üzerinde olduğu tespit edilmiştir. Spor Bilimleri Fakültelerinde görev yapan akademisyenlerin yapay zekaya yönelik genel tutum ölçeğinin, olumlu tutum alt boyutu ile akademik performansa yönelik algı ölçeği arasında pozitif yönde anlamlı bir ilişkinin olduğu tespit edilmiştir. Yapay zeka kullandığının bilinmesinden rahatsızlık duyan akademisyenlerin, akademik performans algıları yapay zeka kullandığının bilinmesinden rahatsızlık duymayan akademisyenlere göre daha düşük düzeydedir. Daha önce yapay zeka kullanmış olan akademisyenlerin akademik performans algılarının daha yüksek olduğu tespit edilmiştir. Sonuçlar, akademisyenlerin yapay zeka teknolojilerine yönelik tutumun, akademik performans üzerinde önemli bir etki yaratma potansiyeline sahip olduğunu göstermektedir
Spor Bilimleri Alanında Çalışan Akademisyenlerin Yapay Zekâya Yönelik Tutumları ile Akademik Performans Algıları
Keywords: Development of Physical Education and Education Programs; Beden Eğitimi ve Eğitim Programlarının Geliştirilmesi